2020
DOI: 10.3390/polym12020290
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Chain Formation of Magnetic Particles in Elastomers with Limited Space

Abstract: The magnetic response of the storage modulus for bimodal magnetic elastomers containing magnetic particles with a diameter of 7.0 μm and plastic beads with a diameter of 200 μm were investigated by varying the volume fraction of plastic beads up to 0.60 while keeping the volume fraction of the magnetic particles at 0.10. The storage modulus at 0 mT for monomodal magnetic elastomers was 1.4 × 104 Pa, and it slightly increased with the volume fraction of plastic beads up to 0.6. The storage modulus at 500 mT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Therefore, the magnetization of ZnO should not affect the remarkable changes in modulus for bimodal elastomers because the magnetization of CI particles was far larger than that of ZnO (70.7 emu/g at 82 mT). The large increase in the storage modulus for the bimodal elastomer is due to the chaining of magnetic particles via nonmagnetic particles as we have presented previously. Since the nonmagnetic particles are immobile even applying magnetic fields, the probability of physical contact between magnetic particles and nonmagnetic particles while making the chain structure . The relative changes in storage modulus for monomodal and bimodal elastomers were 10.2 and 5.1 folds at 80 mT, respectively, which are not much larger than those investigated in our previous studies.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, the magnetization of ZnO should not affect the remarkable changes in modulus for bimodal elastomers because the magnetization of CI particles was far larger than that of ZnO (70.7 emu/g at 82 mT). The large increase in the storage modulus for the bimodal elastomer is due to the chaining of magnetic particles via nonmagnetic particles as we have presented previously. Since the nonmagnetic particles are immobile even applying magnetic fields, the probability of physical contact between magnetic particles and nonmagnetic particles while making the chain structure . The relative changes in storage modulus for monomodal and bimodal elastomers were 10.2 and 5.1 folds at 80 mT, respectively, which are not much larger than those investigated in our previous studies.…”
Section: Resultssupporting
confidence: 53%
“…A bimodal elastomer consists of magnetic particles and nonmagnetic particles. Large changes in storage modulus are obtained by intervening the chain structure of magnetic particles with that of nonmagnetic particles. High loading of both magnetic and nonmagnetic particles increases the number of contacts among particles, resulting in a significant MR effect. Also, bimodal elastomers demonstrate fast response to elasticity changes when a magnetic field is applied .…”
Section: Introductionmentioning
confidence: 99%
“…Tolylene diisocyanate (Fujifilm Wako Chemicals, Ltd.) was used as a linker, and bis­(2-ethylhexyl) phthalate (Fujifilm Wako Chemicals, Ltd.) was used as a plasticizer. The molar ratio of −NCO to the −OH group was constant to be 1.00 (= [NCO]/[OH]), which is the same as those we previously reported. ,,, The prepolymer, PPGs, plasticizer, magnetic particles, and plastic beads were mixed by a spatula for several minutes. The mixed liquid was filled into a silicon mold and cured for 30 min at 100 °C.…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…We have studied thus far methodologies for enhancing the MR effect. In those studies, we investigated the MR effect of polyurethane magnetic elastomers and found that bimodal magnetic elastomers with magnetic and nonmagnetic particles exhibit a significant MR effect compared to monomodal magnetic elastomers. In previous studies, zinc oxide with a diameter of 10.6 μm and aluminum hydroxide with a diameter of 1.4 μm were used as nonmagnetic particles. , When a magnetic field of 500 mT is applied to a bimodal magnetic elastomer with 12 vol % zinc oxide particles, the increase in storage modulus is 500 kPa, which is 4.2 times that of the monomodal (120 kPa) . The increase in the storage modulus of a bimodal magnetic elastomer with 6.6 vol % aluminum hydroxide particles is 3.27 MPa, which is 4.3 times that of the monomodal (754 kPa) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation